Analytics Expo 2022: 121 participants, 20th anniversary and novelties - article Editorial (Разработка и регистрация лекарственных средств)
From April 19 to April 22, the 20th Anniversary International Exhibition of Laboratory Equipment and Chemical Reagents "Analitika Expo 2022" was held at the Crocus Expo IEC.